2014
DOI: 10.1587/transinf.2013edp7395
|View full text |Cite
|
Sign up to set email alerts
|

An Implantable Sacral Nerve Root Recording and Stimulation System for Micturition Function Restoration

Abstract: SUMMARYThis paper provides a prototype neural prosthesis system dedicated to restoring continence and micturition function for patients with lower urinary tract diseases, such as detrusor hyperreflexia and detrusorsphincter dyssynergia. This system consists of an ultra low-noise electroneurogram (ENG) signal recording module, a bi-phasic electrical stimulator module and a control unit for closed-loop bladder monitoring and controlling. In order to record extremely weak ENG signal from extradural sacral nerve r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Countless scientists and clinicians are dedicated to identifying early warning indicators of these diseases. Therefore, physiological signals acquisition [1][2][3][4][5] and processing [6][7][8][9] have become widespread research topics in recent years. Among these diseases, hypertension has a high incidence.…”
Section: Introductionmentioning
confidence: 99%
“…Countless scientists and clinicians are dedicated to identifying early warning indicators of these diseases. Therefore, physiological signals acquisition [1][2][3][4][5] and processing [6][7][8][9] have become widespread research topics in recent years. Among these diseases, hypertension has a high incidence.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the frequency response coefficients at this scale are simple. As shown in Figure 3, the result of transform at scale 2 4 is so clear that it is easy to find the MMP.…”
Section: The Haar Mother Waveletmentioning
confidence: 94%
“…As the analysis in Section 3, there is a delay about 2 j−1 − 1 between the peak in time domain and the zero-crossing point within the MMP in frequency domain. At the scale 2 4 , the delay is about 7 which means the R peak position in time domain is t 1 − 7 . By simulation, it is found that not all the R peaks are in this position.…”
Section: The Ppmmentioning
confidence: 99%
See 1 more Smart Citation